Delay and disruption claims in construction : a practical approach - Haidar, Ali D.; Barnes, Peter, 1954- (ICE Publishing, 2018)
'Delay and Disruption Claims in Construction', third edition is a concise practical guide to the process of delay and disruption presentation and evaluation of claims. The work covers the basics of contract law, breaches of contract, delay and disruption, and resulting loss and expense. It also contains real life case studies with detailed analysis and assessment of the claims presented which offer a practical guide to the presentation of claims.